(untitled) (Research, Society and Development, 2021)
Introduction: Due to the high rate of invasion, malignancy and asymptomatic development, pancreatic cancer is highly lethal. A small number of drugs is available for its approach. Objective: Given this, the present study aims to map the international scientific production on the use of natural products as therapy for pancreatic cancer. Method: Bibliometric research was carried out on academic works on the Web of Science published from 1998 to 2019 using the search terms: "pancreatic cancer", "therapy" and "natural product". After applying the refinement filters, 123 publication records were identified in 82 different journals indexed to the database in question, written by 755 authors who have links to 237 institutions, located in 37 countries. Result: The distribution of the number of publications per year, the most cited and most related journals, the top journals with the most citations, the number of articles by country of origin of the authors’ link institutions, the most cited articles were evaluated. and the co-occurrence of the most cited and most related words. Conclusion: Although recent publications have identified mechanisms of action involved in the interaction of various natural products with pancreatic cancer, we are far from understanding the spectrum of effects that natural therapy has on normal and cancer cells. Further studies on the topic are expected to be carried out and the quantity and quality of publications on the topic are expected to grow even more.